2011
DOI: 10.1111/j.1600-0722.2011.00899.x
|View full text |Cite
|
Sign up to set email alerts
|

An in vitro scanning microradiography study of the reduction in hydroxyapatite demineralization rate by statherin‐like peptides as a function of increasing N‐terminal length

Abstract: Enamel demineralization is slowed by salivary proteins that inhibit calcium hydroxyapatite (HA) demineralization. Statherin (StN43), a 43-residue phosphorylated salivary protein with primary sequence similarities to osteopontin and caseins, binds calcium and HA. The aim of this study was to identify the minimum length of the functional domain of the statherin molecule required for cariostatic function by measuring the efficacy of peptides of progressively shorter length (i.e. containing only the N-terminal 21 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 20 publications
(37 reference statements)
0
22
0
Order By: Relevance
“…In fact, solid-state nuclear magnetic resonance studies confirmed that the N-terminus of statherin strongly binds to hydroxyapatite, while the middle and C-terminal regions are mobile and dynamic [Naganagowda et al, 1998]. In order to protect against demineralization, it is suggested that statherin-like peptides containing at least 15 N-terminal residues or more are required [Shah et al, 2011]. It was recently reported that the calcium concentration in the AEP of patients with dental erosion is 50% reduced, while the concentration of statherin is 35% reduced [Carpenter et al, 2014].…”
Section: Discussionmentioning
confidence: 94%
“…In fact, solid-state nuclear magnetic resonance studies confirmed that the N-terminus of statherin strongly binds to hydroxyapatite, while the middle and C-terminal regions are mobile and dynamic [Naganagowda et al, 1998]. In order to protect against demineralization, it is suggested that statherin-like peptides containing at least 15 N-terminal residues or more are required [Shah et al, 2011]. It was recently reported that the calcium concentration in the AEP of patients with dental erosion is 50% reduced, while the concentration of statherin is 35% reduced [Carpenter et al, 2014].…”
Section: Discussionmentioning
confidence: 94%
“…Details of the SMR technique have been given elsewhere [Anderson et al, 2004;Kosoric et al, 2010;Shah et al, 2011;Mohammed et al, 2013]. The SMR cells containing the samples were mounted on the X-Y stage, which can be moved and repositioned with high precision (±0.5 μm) under computer control.…”
Section: Smr Experimentsmentioning
confidence: 99%
“…However, there is a paucity of data regarding reductions in demineralisation effected by zinc in the literature. Scanning microradiography (SMR) is a real-time X-ray absorption technique which enables directly quantitative, continuous and precise measurements in enamel mineral mass at fixed local positions Elliott, 1985, 1992;Anderson et al, 2004;Shah et al, 2011]. Comparisons of SMR with other measurement techniques have been made elsewhere [Mohammed et al, 2013], but in brief, SMR can be used to continuously measure the physical changes in bulk enamel concentration during the process of demineralisation, in a non-destructive fashion.…”
mentioning
confidence: 99%
“…Peptides such as a statherin‐like peptide have been found to reduce the rate of hydroxyapatite demineralisation in caries‐simulating solutions by 50%. Research efforts have also focused on salivary proteins, which can bind to hydroxyapatite surfaces and form a selectively permeable pellicle. The management of post‐orthodontic white spot lesions is based on remineralisation strategies or minimal‐invasive camouflage of the lesions, micro‐abrasion and resin infiltration.…”
Section: Alloys In Orthodonticsmentioning
confidence: 99%